ESTUDIO DE LA COBERTURA DE RADIOFRECUENCIA DE LA EMISORA RADIO LIBRE 93.9 FM, DE LA CIUDAD DE BABAHOYO, LOS RIOS - Ruíz Salvatierra, Angel Omar (2018)
The 93.9 FM Radioemisora ​​Libre, as a service provider of radio service in the city of Babahoyo and its surroundings, has the need to update the Technical Standard for the Service of Sound Broadcasting in Analogue Modulated Frequency, and with it its service platform, in order to access the concession of the main and auxiliary frequencies, in order to continue with the operation of said station. All this, according to the requirements of the Law, by means of what is regulated in the Regulations for the Adjudication of Qualifying Titles for the operation of Public, Private and Community Social Media and Audio and Video Subscription Systems. This procedure, which is done through the rules of the contest for the award of frequencies of the Sonora Broadcasting Service in Frequency Modulated, in which the coverage area of ​​interest of the petitioner, according to the current regulations, defines the scope of the request. which focuses on obtaining: - Authorization to operate a sound broadcasting studio with the basic components to program the signal, to the interior of the city of Babahoyo, including the use of Analog Subcarriers through an RDS System. - Granting of an auxiliary frequency in the 222- 243 or 246-248 MHz band, with which it operates a radio link from the study of the city of Babahoyo to the main transmitter on the Cochabamba hill. - Concession of the frequency 93.9 MHz to operate the 93.9 FM LIBRE transmitting station in Cerro Cochabamba, with coverage to the main cities of the FR001 operating area. In this way, through this project it is expected to obtain information on the technical requirements necessary to define the radio link system in the Study - Transmitter path and determine the coverage area associated with each transmission system based on the effective radiated power ( PER), as well as the characteristics of the radiant system and the topographic conditions of the locations, by means of the engineering calculation that follows the procedure of Recommendation No. ITU-P-1546, which is a procedure for Point-to-Area predictions.